2006
DOI: 10.1073/pnas.0510188103
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding the genetics of alcohol drinking through transcriptome meta-analysis

Abstract: Much evidence from studies in humans and animals supports the hypothesis that alcohol addiction is a complex disease with both hereditary and environmental influences. Molecular determinants of excessive alcohol consumption are difficult to study in humans. However, several rodent models show a high or low degree of alcohol preference, which provides a unique opportunity to approach the molecular complexities underlying the genetic predisposition to drink alcohol. Microarray analyses of brain gene expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
379
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 326 publications
(396 citation statements)
references
References 36 publications
15
379
1
1
Order By: Relevance
“…The utility of this strategy is provided by recent work that employed a meta-analysis of microarray data from different genetic models of high and low alcohol consumption in their analysis of alcohol preference (Mulligan et al, 2006). This analysis identified genes covering a range of cellular pathways, such as cellular homeostasis and neuronal function, as well as genes with uncharacterized functions.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of this strategy is provided by recent work that employed a meta-analysis of microarray data from different genetic models of high and low alcohol consumption in their analysis of alcohol preference (Mulligan et al, 2006). This analysis identified genes covering a range of cellular pathways, such as cellular homeostasis and neuronal function, as well as genes with uncharacterized functions.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analyses have an important role in identifying many immune-related genes associated with alcohol abuse in both rodents and humans (Kimpel et al, 2007;Liu et al, 2006;Mulligan et al, 2006). Validating several candidate genes from these studies (including Cd14, Il1ra, and Il6) through single-gene null mutations in mice confirmed that knockout of each gene resulted in decreased alcohol consumption on a two-bottle choice test (Blednov et al, 2012).…”
Section: Alcohol Glia and Neuroimmune Signalingmentioning
confidence: 96%
“…In a separate comparison of expression data between a B6.D2 congenic line and the B6 background, Zfp291 showed reduced expression in high ethanol-consuming lines. 36 Zfp291 contains a U1 subclass ZNF domain characteristic of RNA binding proteins 37 and maps to the strongest alcohol preference QTL in B6-and D2-derived populations, found on mouse chromosome 9. We are following up the present study in several ways.…”
Section: Discussionmentioning
confidence: 99%